2015
DOI: 10.1371/journal.pone.0122179
|View full text |Cite
|
Sign up to set email alerts
|

Stanniocalicin 2 Suppresses Breast Cancer Cell Migration and Invasion via the PKC/Claudin-1-Mediated Signaling

Abstract: Stanniocalcin (STC), a glycoprotein hormone, is expressed in a wide variety of tissues to regulate Ca2+ and PO4- homeostasis. STC2, a member of STC family, has been reported to be associated with tumor development. In this study, we investigated whether the expression of STC2 is associated with migration and invasion of breast cancer cells. We found that breast cancer cell line 231 HM transfected with STC2 shRNA displayed high motility, fibroblast morphology, and enhanced cell migration and invasion. Introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 40 publications
(46 reference statements)
1
51
0
Order By: Relevance
“…However, given its role in promoting lymphovascular invasion and regional metastasis, other studies have shown that Snail may also be used as a molecular prognostic marker for HNSCC [41, 42]. Although Hou et al reported that STC2 may inhibit EMT in human breast cancer cells [43], our results suggest that the interaction between Snail and the PI3K/AKT pathway may mediate STC2-induced HNSCC metastasis. Similarly, the expression patterns of STC2, pAKT, Snail, vimentin, and E-cadherin in HNSCC tissues were consistent with those in cells, implying that STC2 plays an oncogenic role in HNSCC.…”
Section: Discussionmentioning
confidence: 53%
“…However, given its role in promoting lymphovascular invasion and regional metastasis, other studies have shown that Snail may also be used as a molecular prognostic marker for HNSCC [41, 42]. Although Hou et al reported that STC2 may inhibit EMT in human breast cancer cells [43], our results suggest that the interaction between Snail and the PI3K/AKT pathway may mediate STC2-induced HNSCC metastasis. Similarly, the expression patterns of STC2, pAKT, Snail, vimentin, and E-cadherin in HNSCC tissues were consistent with those in cells, implying that STC2 plays an oncogenic role in HNSCC.…”
Section: Discussionmentioning
confidence: 53%
“…STC2, a secreted glycoprotein hormone expressed by a variety of tissues, regulates calcium and phosphate homeostasis, inhibits apoptosis and oxidative damage, and induces proliferation [43,44]. STC2 has recently been described to inhibit epithelial-mesenchymal transition through the PKC/claudin-1-mediated signaling in human breast cancer cells [45]. Previous studies have shown deregulated expression of STC2 in a variety of cancers, with its expression correlating with poor prognosis [45][46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…The protein concentrations of the lysates were measured with a Bio-Rad protein assay kit (Hercules, CA). Immunoblot analyses were performed as previously described [37, 38]. β-Actin antibodies were obtained from Santa Cruz Biotechnology.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor inoculation assays in nude mice have been described previously [3738]. Briefly, a total of 4 × 10 6 −1 × 10 7 231 PCDH cells or 231 PCDH HER2 cells suspended in 100 μl of sterile phosphate-buffered saline (PBS) were injected subcutaneously into the right hind legs of 24 male BALB/c athymic mice.…”
Section: Methodsmentioning
confidence: 99%